Pulsed electric field and pre-heating treatment effect on free fatty acid (FFA), pH, vitamin C, and organoleptic properties of milk - Teti Estiasih; Angky Wahyu Putranto; Anugerah Dany Priyanto; Widyasari Widyasari; Pardi Sampe Tola (Advances in Food Science, Sustainable Agriculture and Agroindustrial Engineering (AFSSAAE), 2023)
The pulsed electric field (PEF)has been extensively studied in milk processing. However, treatment conditions still need to be improved to meet safety for consumption. This study aimed to determine optimum conditions by varying PEF and preheating treatment time. Free fatty acids (FFA), pH, and vitamin C are used to assess the milk quality. Preheating temperature is fixed at 70Â°C and the treatment time: 10, 20, and 30 minutes. PEF parameters are Â electric field, 66 Î¼s pulse width, and the applied time of 2, 4, and 6 minutes. The pH value and preheating treatment time show a negative linear relationship in the range of 6.75-7.15, while PEF treatment time did not significantly affect pH. The FFA linearly increases as preheating treatment time increases from 0.0053-0.0097%. Vitamin C decreases as preheating treatment time increase from 0.003-0.0049 mg/ml. PEF treatment significantly affects vitamin C, where vitamin C decreases as treatment time increases. Preheating and PEF treatment time show positive effects on the organoleptic properties of milk. The organoleptic properties values are flavor 3.93, aroma 4.00, and color 3.9 out of 5.